Interval post-colonoscopy colorectal cancer following a negative colonoscopy in a fecal immunochemical test-based screening program - van de Schootbrugge-Vandermeer, Hilliene J.; Kooyker, Arthur I.; Wisse, Pieter H. A.; Nagtegaal, Iris D.; Geuzinge, Hiltje A.; Toes-Zoutendijk, Esther; de Jonge, Lucie; Breekveldt, Emilie C. H.; van Vuuren, Anneke J.; van Kemenade, Folkert J.; Ramakers, Christian R. B.; Dekker, Evelien; Lansdorp-Vogelaar, Iris; Spaander, Manon C. W.; van Leerdam, Monique E. (Endoscopy, 2023)
Background In the Dutch colorectal (CRC) screening program, fecal immunochemical test (FIT)-positive individuals are referred for colonoscopy. If no relevant findings are detected at colonoscopy, individuals are reinvited for FIT screening after 10 years. We aimed to assess CRC risk after a negative colonoscopy in FIT-positive individuals.Methods In this cross-sectional cohort study, data were extracted from the Dutch national screening information system. Participants with a positive FIT followed by a negative colonoscopy between 2014 and 2018 were included. A negative colonoscopy was defined as a colonoscopy during which no more than one nonvillous, nonproximal adenoma < 10 mm or serrated polyp < 10 mm was found. The main outcome was interval post-colonoscopy CRC (iPCCRC) risk. iPCCRC risk was reviewed against the risk of interval CRC after a negative FIT (FIT IC) with a 2-year screening interval.Results 35 052 FIT-positive participants had a negative colonoscopy and 24 iPCCRCs were diagnosed, resulting in an iPCCRC risk of 6.85 (95 %CI 4.60–10.19) per 10 000 individuals after a median follow-up of 1.4 years. After 2.5 years of follow-up, age-adjusted iPCCRC risk was approximately equal to FIT IC risk at 2 years.Conclusion Risk of iPCCRC within a FIT-based CRC screening program was low during the first years after colonos-copy but, after 2.5 years, was the same as the risk in FIT-negative individuals at 2 years, when they are reinvited for screening. Colonoscopy quality may therefore require further improvement and FIT screening interval may need to be reduced after negative colonoscopy.